2016
DOI: 10.1186/s13756-016-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug susceptibility patterns of the Mycobacterium tuberculosis isolated from previously treated and new cases of pulmonary tuberculosis at German-Nepal tuberculosis project laboratory, Kathmandu, Nepal

Abstract: BackgroundMultidrug resistant tuberculosis (MDR-TB) is a serious public health problem in Nepal. It is a major obstacle for the control of the tuberculosis. The main objectives of this study were to determine the prevalence of the multidrug resistant pulmonary tuberculosis and to evaluate the drug susceptibility patterns of Mycobacterium tuberculosis isolated from previously treated and newly diagnosed cases of pulmonary tuberculosis.MethodsA cross-sectional study was conducted from March 2013 to August 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
9
3
Order By: Relevance
“…Drug resistant cases detected in this study was less than the research conducted by Thapa et al (2016) in German-Nepal tuberculosis project laboratory which showed 31.1% of DR cases. Maharjan et al (2017) also noted 37.2% DR cases.The MDR strains prevalence in TB patients in this study was similar to previous studies (Thapa 2016;NTC 2016), but slightly higher than the research conducted in 2011 (7.9%) and 2015 (11.7%) (Maharjan et al 2017;Wagley et al 2016). This implies MDR strains prevalence in TB patients is continually increasing which poses a serious public health problem due to poor patient management, non-adherence to the prescribed regimen, irregular supply of drugs, poor quality of drugs and poor national TB control programme.…”
Section: Discussioncontrasting
confidence: 72%
“…Drug resistant cases detected in this study was less than the research conducted by Thapa et al (2016) in German-Nepal tuberculosis project laboratory which showed 31.1% of DR cases. Maharjan et al (2017) also noted 37.2% DR cases.The MDR strains prevalence in TB patients in this study was similar to previous studies (Thapa 2016;NTC 2016), but slightly higher than the research conducted in 2011 (7.9%) and 2015 (11.7%) (Maharjan et al 2017;Wagley et al 2016). This implies MDR strains prevalence in TB patients is continually increasing which poses a serious public health problem due to poor patient management, non-adherence to the prescribed regimen, irregular supply of drugs, poor quality of drugs and poor national TB control programme.…”
Section: Discussioncontrasting
confidence: 72%
“…Of 60 tuberculosis positive cases, 2 (3.33%) were MDR-TB cases. However, higher rate of MDR pulmonary tuberculosis was reported by Thapa et al (15.6 %) [6]. This may be because of including only smear negative suspected tuberculosis cases in our study.…”
Section: Dear Editorcontrasting
confidence: 57%
“…16 Other reported MDR tuberculosis rates from South East Asia include 15.6% from Nepal. 17 African countries are not among the top three countries associated with over half the global burden of MDR tuberculosis. 18 The MDR tuberculosis rates from this region have varied, with a range of rates reported: 4.5% from Chad, 19 12.0% from Benin, 20 5.1% from Mozambique, 21 18% from Cameroon, 22 11.5% from Djibouti, 23 and 1.2% and 3.37% from Ethiopia, 24,25 which are generally higher than the rate observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of MDR tuberculosis are generally reported in retreatment cases as opposed to newly diagnosed cases. 14,17,25,26…”
Section: Discussionmentioning
confidence: 99%